2022
DOI: 10.1088/1361-6439/ac7ea6
|View full text |Cite
|
Sign up to set email alerts
|

PDMS membrane-based flexible bi-layer microfluidic device for blood oxygenation

Abstract: We report the fabrication and experimental study of a flexible bi-layer microfluidic device for blood oxygenation, mimicking the thin alveolar exchange barrier constituting a lung. A facile technique is employed to fabricate the device by sandwiching a thin polymeric membrane as the gas exchange layer between two flexible microchannels. A numerical model coupling the mass, momentum, and species transport equations, is used to simulate oxygen diffusion between the blood and oxygen channels across the gas exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The width and interelectrode spacing are kept fixed at 20 μm which gives a resonant frequency of 49.98 MHz. To avoid direct electrical connections between the ice and the IDTs, thin polydimethylsiloxane (PDMS) film of 20 μm thickness is fabricated and placed over the IDTs and the lead wires. With such thin PDMS layers, the attenuation of SAW power due to the presence of a PDMS layer is found to be negligible .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The width and interelectrode spacing are kept fixed at 20 μm which gives a resonant frequency of 49.98 MHz. To avoid direct electrical connections between the ice and the IDTs, thin polydimethylsiloxane (PDMS) film of 20 μm thickness is fabricated and placed over the IDTs and the lead wires. With such thin PDMS layers, the attenuation of SAW power due to the presence of a PDMS layer is found to be negligible .…”
Section: Methodsmentioning
confidence: 99%
“…With such thin PDMS layers, the attenuation of SAW power due to the presence of a PDMS layer is found to be negligible. 39 The thin layer of PDMS is applied by spin coating a mixture of liquid PDMS with a base-to-curing agent ratio of 1:10 over a glass slide at 4000 rpm for 10 s using a spin coater 38 after which it is peeled off and placed over the IDTs.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Hollow fiber membranes have been used as an oxygenator and are usually obtained via a phase inversion process [ 191 , 192 ]. The commonly used polymers for hollow fiber membranes are hydrophobic polymers, such as polymethylpentene (PMP), polypropylene (PP), PDMS, polysulfone (PSf), polyethersulfone (PES), polyethylene (PE) and polyvinylidene fluoride (PVDF) [ 26 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ]. Wang et al [ 194 ] reported the production of poly (4-methyl-1-pentene)/polypropylene (PMP/PP) thin film composite (TFC) with a PVA/PSS coating was anchored on the membrane surface via crosslinking and PDA binding for membrane oxygenator application.…”
Section: Biomedical Applications Of Membranesmentioning
confidence: 99%
“…In severe liver dysfunction, toxins might build up in the blood and lead to hepatic encephalopathy, potentially leading to multi-organ failure [ 8 ]. This can be addressed by artificial devices similar to dialysis [ 9 ] and blood oxygenator [ 10 ] systems. These devices work by recapitulating liver functions within a synthetic liver that is capable of adsorption and filtering as an artificial liver support device [ 11 ].…”
Section: Introductionmentioning
confidence: 99%